UNRAVELING THE CHALLENGES OF UNDERACHIEVING STUDENTS IN LEARNING ENGLISH - Maharani, Ida Ayu; Purnama, I Gusti Agung Vony (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study explored the nuanced experiences of underachieving students in English language learning. Two data collection techniques were used in this research: quantitative data obtained from the questionnaire and the qualitative data gained from the semi-structured interview. This study involved 96 students (three classes) in the second semester in English Class of ITB STIKOM Bali. The interview was conducted and two distinct type of underachieving students were found: coasting underachievers and anxious underachievers. Coasting underachievers demonstrate disengagement and lack of motivation, while anxious underachievers exhibit high levels of anxiety and self-doubt. Furthermore, based on the questionnaire result, it was found that tailored interventions addressing the specific needs of each type are crucial for fostering academic success and personal fulfillment. The analysis reveals significant factors influencing students' participation, self-perceived proficiency, and challenges in language acquisition. Understanding these factors enables educators to create inclusive learning environments and implement targeted support strategies. Students express preferences for various forms of support, highlighting the importance of personalized, holistic approaches to English language learning. Leveraging these insights, educators can empower underachieving students to thrive academically and develop essential language skills for success in university and beyond. Keywords: underachieving students; challenges; learning English